Gastroparesis: New insights into an old disease - Usai-Satta, Paolo (World J Gastroenterol, 2020)
Gastroparesis (Gp) is a chronic disease characterized by a delayed gastric emptying in the absence of mechanical obstruction. Although this condition has been reported in the literature since the mid-1900s, only recently has there been renewed clinical and scientific interest in this disease, which has a potentially great impact on the quality of life. The aim of this review is to explore the pathophysiological, diagnostic and therapeutical aspects of Gp according to the most recent evidence. A comprehensive online search for Gp was carried out using MEDLINE and EMBASE. Gp is the result of neuromuscular abnormalities of the gastric motor function. There is evidence that patients with idiopathic and diabetic Gp may display a reduction in nitrergic inhibitory neurons and in interstitial cells of Cajal and/or telocytes. As regards diagnostic approach, 99-Technetium scintigraphy is currently considered to be the gold standard for Gp. Its limits are a lack of standardization and a mild risk of radiation exposure. The C13 breath testing is a valid and safe alternative method. (13)C acid octanoic and the (13)C Spirulina platensis recently approved by the Food and Drug Administration are the most commonly used diagnostic kits. The wireless motility capsule is a promising technique, but its use is limited by costs and scarce availability in many countries. Finally, therapeutic strategies are related to the clinical severity of Gp. In mild and moderate Gp, dietary modification and prokinetic agents are generally sufficient. Metoclopramide is the only drug approved by the Food and Drug Administration for Gp. However, other older and new prokinetics and antiemetics can be considered. As a second-line therapy, tricyclic antidepressants and cannabinoids have been proposed. In severe cases the normal nutritional approach can be compromised and artificial nutrition may be needed. In drug-unresponsive Gp patients some alternative strategies (endoscopic, electric stimulation or surgery) are available.